The estimation of atmospheric water vapour during monsoon season in northern region of Peninsular Malaysia - Mohmad Lehan, Nur Fadzlina Aini (2012)
Water vapour plays a significant role in the physical and chemical processes of the atmosphere. It is also considered as one of the major contributors to the greenhouse effect. Analyses of the water vapour would contribute greatly to atmospheric studies, such as weather forecasting and climate monitoring. With the rapid development of Global Positioning System (GPS), it will continuously provide a source of global data that can be used to extract tropospheric parameters. One of the parameters, the Zenith Wet Delay (ZWD), can be computed to Integrated Water Vapour (IWV) using an interpolation method with the surface meteorological data since there is no adjacent surface meteorological sensor located at the ground based GPS stations used in this study. One month data and every 15th day were processed to represent each monsoon season from four MyRTKnet stations and four Malaysia Meteorological Department (MMD) stations using the Bernese v5.0 software. A MATLAB programming was used to compute the GPS IWV and the plotting variation of water vapour during the monsoon seasons in northern region of Peninsular Malaysia. As Peninsular Malaysia is located in low latitude region, the result shows the water vapour amount is higher during the Northeast monsoon due to the heavy rains and the wind prevailing. Meanwhile, East coast of Peninsular Malaysia tends to get the higher value of rainfall and the water vapour values were higher compare to west coast area of Peninsular Malaysia. The result shows a strong relationship between the rainfall distribution and the water vapour values with the correlation range of 90% to 99% for every monsoon to prove that high rainfall values usually occurred with high water vapour amounts in these areas.